Managing care errors in the wards: The contribution of authentic leadership and error management culture. Issue 1 (11th February 2019) - Farnese, Maria Luisa; Zaghini, Francesco; Caruso, Rosario; Fida, Roberta; Romagnoli, Manuel; Sili, Alessandro
Abstract : Purpose: The importance of an error management culture (EMC) that integrates error prevention with error management after errors occur has been highlighted in the existing literature. However, few empirical studies currently support the relationship between EMC and errors, while the factors that affect EMC remain underexplored. Drawing on the conceptualisation of organisational cultures, the purpose of this paper is to verify the contribution of authentic leadership in steering EMC, thereby leading to reduced errors. Design/methodology/approach: The authors conducted a cross-sectional survey study. The sample included 280 nurses. Findings: Results of a full structural equation model supported the hypothesised model, showing that authentic leadership is positively associated with EMC, which in turn is negatively associated with the frequency of errors. Practical implications: These results provide initial evidence for the role of authentic leadership in enhancing EMC and consequently, fostering error reduction in the workplace. The tested model suggests that the adoption of an authentic style can promote policies and practices to proactively manage errors, paving the way to error reduction in the workplace. Originality/value: This study was one of the first to investigate the relationship between authentic leadership, error culture and errors. Further, it contributes to the existing literature by demonstrating both the importance of cultural orientation in protecting the organisation from error occurrence and the key role of authentic leaders in creating an environment for EMC development, thus permitting the organisation to learn from errors and reduce their negative consequences.